On cosmopolitan translation and how worldviews might change - Pym, Anthony (Stellenbosch Papers in Linguistics Plus, 2021)
The theorisation of cosmopolitanism can be dated from Kant’s “right to hospitality”, where the reciprocal welcoming of foreigners is supposed to lead to universal understanding. Differences in languages and religions are recognised as obstacles in the way to that ideal, yet Kant has little to say about how to get around their differences – translation is strangely absent. A role for translation in cosmopolitanism nevertheless appears in the discourses that assume an age of effective economic globalisation. The cosmopolitanisms elaborated on by Ulrich Beck (2004/2006) and Gerard Delanty (2009), among many others, adopt a sense of cultural translation that requires no anterior text, no language barrier, and thus no mediator: the cosmopolitan becomes an intercultural space where relations transform subjects. Those views may be tested on the narratives of three Afrikaans-speaking intellectuals who recount how they grew up under Apartheid and progressively dissented from totalitarian discourse. The concepts of cosmopolitan translation are found to explain some of the narratives involved, particularly when the self is seen through the eyes of the other, yet strong social and national frames are still in force, boycotts counter hospitality and reinforce national frames, and language translation is found to be relatively unimportant in a milieu of polyglots.